Penerapan Sistem Tumpang Sari Kopi Robusta dan Nilam sebagai Upaya Diversifikasi Usaha Tani di Desa Teuladan - Putera, Muzakkir; Zulfan, Zulfan; Wiguna, Husein Sadewa; Fajri, Muhammad Iqbal; Riady, Muhammad Antos; Newton, Newton (Pencerah, 2025)
Desa Teuladan, located in kecamatan Lembah Seulawah, Aceh Besar Regency, has long been known as a center for patchouli cultivation, which has become the main source of income for the local community. However, limited processing facilities, particularly the lack of patchouli oil distillation equipment, have posed serious obstacles, leading to decreased farmer incomes. In an effort to maintain economic sustainability, some farmers have started to switch to cultivating robusta coffee, which is considered more stable in terms of market demand and selling price. Nevertheless, the desire to preserve patchouli as an identity commodity of the village remains strong. This community service activity was carried out to assist farmers in optimizing land use through the application of an intercropping system combining robusta coffee and patchouli. The stages of the activity included socialization of the intercropping concept, training on integrated cultivation techniques, preparation of seedlings, and discussions with farmers regarding the selection of appropriate planting patterns. Based on group discussions, the border method was considered easier to understand and apply, and more suitable for land conditions with existing natural shade trees. Therefore, the probability of adopting the border method as the main planting pattern is estimated at around 80%. This initiative is expected not only to help improve land productivity and diversify income but also to strengthen farmers’ capacity in managing a more adaptive and sustainable cultivation system.